2019
DOI: 10.1155/2019/3563761
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Application for Predicting Soil Organic Matter Content by VIS-NIR Spectroscopy

Abstract: Deep learning is characterized by its strong ability of data feature extraction. This method can provide unique advantages when applying it to visible and near-infrared spectroscopy for predicting soil organic matter (SOM) content in those cases where the SOM content is negatively correlated with the spectral reflectance of soil. This study relied on the SOM content data of 248 red soil samples and their spectral reflectance data of 400–2450 nm in Fengxin County, Jiangxi Province (China) to meet three objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…39 It is used by some scholars in the eld of spectroscopy. 40,41 In the eld of spectroscopy, the one-dimensional (1D) CNN model is used to learn and predict spectra, and has achieved good performances. 1D CNN is a non-linear model; however, given a spectrum (SPEC) of category c, it can be expanded by calculating the rst-order Taylor approximation to approximate the score value S c (SPEC) with a linear function.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…39 It is used by some scholars in the eld of spectroscopy. 40,41 In the eld of spectroscopy, the one-dimensional (1D) CNN model is used to learn and predict spectra, and has achieved good performances. 1D CNN is a non-linear model; however, given a spectrum (SPEC) of category c, it can be expanded by calculating the rst-order Taylor approximation to approximate the score value S c (SPEC) with a linear function.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…The hierarchical structure and high learning capacity make DNN models quite flexible and adaptable for a wide variety of highly complex problems such as SOC prediction [11,39,40]. The DNNs have recently been used for the prediction of soil properties [40][41][42] and particularly for SOC prediction [43,44]. Xu et al [43], for instance, indicated that the DNN method had a high performance for the prediction of SOC with the effective abstraction of complex covariates for learning by using visible and near-infrared soil spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the technology for the rapid detection of SOM content in soil has been a hot topic in the soil research community within the past couple decades [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Visible-near infrared (Vis-NIR) spectroscopy has been a simple and efficient analytical technique which has been widely deployed for the detection of SOM content [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The high sensitivity of vis-NIR spectroscopy has been shown to be capable to detect trace minerals such as arsenic contamination in soil [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these studies [ 27 , 28 , 29 , 30 , 31 , 32 , 40 ] the best coefficient of determination ( R 2 ) and the ratio of prediction to deviation (RPD) for assessing the SOM in moist soil (<35% w / w moisture) were about 0.86–0.88 [ 27 ] and 2.66 [ 29 ] respectively. Note that the assessments of SOM from relatively dry soil have achieved much better result with R 2 and RPD of 0.892 ± 0.004 and 3.053 ± 0.056 respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%